Mengubah Gambar Sketsa Menjadi Visual yang Menakjubkan : Membangun Dunia Animasi dengan Kecerdasan Buatan - Warman, Rahmat Aditya (Journal of Animation and Games Studies, 2024)
The rapid development of technology in the current era has brought changes to the industry of animation. The utilization of artificial intelligence technology in the field of animation helps accelerate the creative process of creating animated films, one of which is the search for visual concepts to be used. The search for visual concepts can now be made using only sketch images through the assistance of artificial intelligence. The research method employed is exploration, and this study will explore the utilization of Control Trait on the artificial intelligence platform used, namely Playground AI. The sketch images used consist of 10 images, comprising 5 character sketch images and 5 environmental sketch images. The results of the research reveal that the recommended Control Trait values for sketch images fall within the range of 0.4 – 0.6. The conclusion of this study is that black and white sketch images can be quickly transformed into stunning visuals with the assistance of artificial intelligence. The generated images are sufficiently good to be used as visual concepts for an animated film.